1997
DOI: 10.1172/jci119524
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic origin of cholesteryl oleate in coronary artery atherosclerosis in African green monkeys. Enrichment by dietary monounsaturated fat.

Abstract: Relationships among plasma lipoprotein cholesterol, cholesterol secretion by the isolated, perfused liver, and coronary artery atherosclerosis were examined in African green monkeys fed diets containing cholesterol and 35% of calories as fat enriched in polyunsaturated, monounsaturated, or saturated fatty acids. The livers of animals fed monounsaturated fat had significantly higher cholesteryl ester concentrations (8.5 mg/g wet wt) than the livers of the other diet groups (3.65 and 3.37 mg/g wet wt for saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 46 publications
8
63
0
Order By: Relevance
“…Previous studies in non-human primates have documented a strong correlation between hepatic CE content and hepatic CE secretion rate (22) and LDL particle size (23), both of which are highly correlated with coronary artery atherosclerosis (22,24,25). To determine whether LCAT deficiency, which resulted in increased aortic cholesterol deposition, also resulted in increased hepatic cholesterol deposition, we quantified EC and FC in the livers of the study animals ( …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in non-human primates have documented a strong correlation between hepatic CE content and hepatic CE secretion rate (22) and LDL particle size (23), both of which are highly correlated with coronary artery atherosclerosis (22,24,25). To determine whether LCAT deficiency, which resulted in increased aortic cholesterol deposition, also resulted in increased hepatic cholesterol deposition, we quantified EC and FC in the livers of the study animals ( …”
Section: Resultsmentioning
confidence: 99%
“…However, the compositional data in Table III argue against this interpretation because there is no observable increase in the proportion of FC and PL in the plasma apoB lipoproteins. Our previous studies in non-human primates have shown a strong correlation between hepatic CE content and the concentration of VLDL CE in recirculating liver perfusate, suggesting that hepatic CE storage pools are coupled to VLDL CE secretion (22,23). However, the amount of hepatic CE was similar for both apoEϪ/Ϫ and apoEϪ/Ϫ LCATϪ/Ϫ mice (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Rudel and colleagues (25,26) have recently used two animal models to compare the effects of various dietary fats on atherosclerosis. In their first study they fed adult male African green monkeys for 5 years with experimental diets containing 35% of calories as fat enriched in palm oil (SFA), oleic acid-enriched safflower oil (MUFA), or safflower oil (PUFA) and Ϸ0.4% (wt͞wt) cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were immediately frozen in liquid nitrogen and stored at Ϫ80°C until analyzed. At the end of an atherosclerosis progression period of 3 years in cynomolgus monkeys and 5 years in green monkeys, during which the high cholesterol diet was fed, livers were removed from the animals, and recirculating perfusion was performed as described previously (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…Instead, cholesterol esterification enzymes are candidate sites for regulation. We have shown that when atherogenic diets are fed to primates, the extent of hepatic cholesteryl ester secretion in response to dietary fatty acids is highly correlated to the extent of CAA (10). Hepatic cholesteryl ester secretion in apoB-containing lipoproteins in primates is facilitated by hepatic acyl-coenzyme A:cholesterol acyltransferase (ACAT) (11), and the form of ACAT enzyme present in the hepatocyte is ACAT2 (12,13).…”
mentioning
confidence: 99%